Characterization of a Lipase From the Silkworm Intestinal Bacterium Bacillus pumilus With Antiviral Activity Against Bombyx mori (Lepidoptera: Bombycidae) Nucleopolyhedrovirus In Vitro. Issue 6 (5th November 2018) - Liu, Renhua; Wang, Wenhui; Liu, Xiaoyuan; Lu, Yan; Xiang, Tingting; Zhou, Wei; Wan, Yongji
Abstract: To investigate whether Bombyx mori Linnaeus (Lepidoptera: Bombycidae) intestinal microorganism play a role in the host defence system against viral pathogens, a lipase gene from the silkworm intestinal bacterium Bacillus pumilus SW41 was characterized, and antiviral activity of its protein against B. mori nucleopolyhedrovirus (BmNPV) was tested. The lipase gene has an open-reading frame of 648 bp, which encodes a 215-amino-acid enzyme with a 34-amino-acid signal peptide. The recombinant lipase (without signal peptide) was expressed and purified by using an Escherichia coli BL21 (DE3) expression system. The total enzyme activity of this recombinant lipase reached 277.40 U/mg at the optimum temperature of 25°C and optimum pH value of 8.0. The antiviral test showed that a relative high concentration of the recombinant lipase reduced BmNPV infectivity in vitro, which resulted in decreased viral DNA abundance and viral occlusion bodies. Besides, the preincubation method also suggested that the lipase probably directly acting on the budded virions. The results suggest that the lipase from intestinal bacterium B. pumilus SW41 is a potential antiviral factor for silkworm against BmNPV.